Pengaruh Kepemimpinan dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Lazada Ekpres Gudang (Hub) Pondok Cabe Tangerang Selatan - Khanif Nur I’zaaz; Aden Prawiro Sudarso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of Leadership and Work Stress on Employee Performance at PT Lazada Ekpres Warehouse (Hub) Pondok Cabe South Tangerang. The method used is a quantitative method with a descriptive approach. The sampling technique used was Non Probability sampling with a sample of 55 respondents. In collecting data using observation techniques and distributing questionnaires. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research are that leadership has a significant effect on employee performance with the regression equation Y = 13.243 + 0.668 X1. The correlation coefficient value for the Leadership variable is 0.711, meaning that the two variables have a strong level of relationship with a coefficient of determination of 50.5%. Hypothesis testing obtained a value of tcount > ttable or (7.356 > 0.266). Thus Ho1 is rejected and Ha1 is accepted. This means that there is a significant influence between Leadership and Employee Performance. Job Stress has a significant effect on Employee Performance with the regression equation Y = 11.873 + 0.614 X2. The Job Stress correlation coefficient value is 0.820, meaning that the two variables have a very strong level of relationship with a coefficient of determination of 59.5%. Hypothesis testing obtained a value of tcount > ttable or (8.816 > 0.266). Thus, H02 is rejected and Ha2 is accepted, meaning that there is a significant influence between Job Stress on Employee Performance. Leadership and Job Stress have a significant effect on employee performance with the regression equation Y= 6.696 + 0.344 X1 + 0.426 X2. The correlation coefficient value is 0.820, meaning that the independent variable and the related variables have a very strong level of relationship with a coefficient of determination of 67.3%. Hypothesis testing obtained a value of fcount > ftable or (53.538 > 3.17). Thus, Ho3 is rejected and Ha3 is accepted, meaning that there is a significant simultaneous influence between Leadership and Job Stress on Employee Performance at PT. Lazada Express Warehouse (Hub) Pondok Cabe South Tangerang.